Efficient Extraction of Past Seawater Pb and Nd Isotope Signatures From Southern Ocean Sediments - Huang, H.; Gutjahr, M.; Kuhn, G.; Hathorne, Ed C.; Eisenhauer, A.; Gutjahr, M.; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Kuhn, G.; 2 Alfred‐Wegener‐Institut Helmholtz‐Zentrum für Polar‐ und Meeresforschung Bremerhaven Germany; Hathorne, Ed C.; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany; Eisenhauer, A.; 1 GEOMAR Helmholtz Centre for Ocean Research Kiel Kiel Germany (Geochemistry, Geophysics, Geosystems, 2021)
Radiogenic lead (Pb) and neodymium (Nd) isotope compositions extracted from authigenic phases in marine sediments are sensitive tracers to reconstruct past ocean circulation and water mass mixing. Chemical reductive leaching of hydrogenetic ferromanganese oxyhydroxides from bulk sediments is the most practical way to recover past seawater Pb and Nd isotope signatures in the Southern Ocean, due to the scarcity of alternative archives. However, the leached signal could be compromised if substantial quantities of Pb and Nd were released from non‐hydrogenetic sediment fractions during chemical extraction. Here we developed a very short 10‐s leaching method to extract reliable seawater Pb and Nd isotope signals from sediments in the Atlantic sector of Southern Ocean. The effect of a previously recommended MgCl2 pre‐wash, the role of chelate ligands in the leaching solution and length of leaching time were investigated. The results show that 10‐s exposure time of sediments to reductive leaching extracted sufficient and more reliable hydrogenetic Pb and Nd compared with the commonly used 30‐min leaching approaches. The robustness of our improved leaching method was validated via direct comparison of Pb and Nd isotope signatures with actual seawater, porewater, and corresponding sediment leachates from three stations in front of the Antarctic Filchner‐Rønne Ice Shelf. Our findings also indicate that in contrast previously studied sites on the West Antarctic continental shelf, the bottom seawater Nd concentration is less elevated through benthic fluxes in the area of the southern Weddell Sea shelf. Plain Language Summary: Individual modern ocean water masses can often be identified by the isotopic signature of dissolved trace metals lead (Pb) and neodymium (Nd) supplied from surrounding continents. By analyzing past seawater Pb and Nd isotope ratios preserved in the sedimentary archives, we can understand how the ocean circulation changed. In the Southern Ocean, archives preserving past seawater Pb and Nd isotope ...